RATING EVALUATION OF ACTIVITIES OF BANKS OF UKRAINE AT THE MODERN STAGE - Грудзевич, Уляна (Socio-economic relations in the digital society, 2019)
A rating evaluation of activity of banks is one of directions of estimation of financial firmness and largelyinfl uences on perception of bank investors, depositors, creditors. In Ukraine a rating evaluation is conducted after a few directions: rating estimation of banks by the National bank of Ukraine, rating agencies, Ministry of finance of Ukraine and news agencies that have own methodologies, however as arule use the typical enough list of indexes. The present state and problems of the banks’ rating assessment by the National Bank of Ukraine on the CAMELSO system are investigated. Th is system is closed, inaccessible to a wide range of users, but allows the NBU to accurately assess the fi nancial position of the bank according to a standardized system of indicators The determination of the credit rating by international and national authorized rating agencies and the rating of financial stability of banks according to the methodology of the Ministry of Finance of Ukraine are researched. Methodology and efficiency of rating evaluation of the indicatedsubject of ratings are compared. The credit rating and rating of reliability of deposits, appropriated by national and international agencies to the home banks, is analysed. It was revealed that all rating agencies updated their methodology for assessing banks. There is a tendency for banks to receive ratings from several rating agencies. Mostly, banks that received ratings of international rating agencies are in groups of state, or in banks of foreign banking groups. Ratings of banks provided by international rating agencies on a global scale have a speculative class. Private equity banks are rated only by one of the national rating agencies andas a rule most of them have an investment grade. The prospects of rating assessment of banks at the present stage are determined, among which rating ratings of banks from several rating agencies, which will allow to confi rm their reliability; improvement of the legislative and regulatory framework, including the adoption of the Law «On Ratings».
Keywords: rating; rating evaluation; rating of borrowers; rating of debt instruments; rating of deposit reliability